Internal workload in elite female football players during the whole in-season: starters vs non-starters - Romero-Moraleda, B.; González-García, J.; Morencos, E.; Giráldez-Costas, V.; Moya, J. M.; Ramirez-Campillo, R. (Biology of Sport, 2023)
The aim of this study was to quantify weekly internal workload across the in-season and compare the workload variables between starter and non-starter Spanish female first league (Liga Iberdrola) football players. Twenty-six participants belonging to the same team (age, height, and mass: 25.4 ± 6.1 years, 167.4±4.8 cm and 57.96±6.28 kg, respectively) participated in this study. Training loads (TL) and match loads (ML) were assessed through breath-cardiovascular (RPEbreath), leg-musculature (RPEleg) and cognitive (RPEcog) rating of perceived exertion (RPE0-10) for each training session and match during the in-season phase (35 weeks). Session-RPE (sRPE) was calculated by multiplying each RPE value by session duration (minutes). From these, total weekly TL (weekly TL+ML), weekly TL, weekly ML, chronic workload, acute:chronic workload ratio, training monotony, and training strain were calculated. Linear mixed models were used to assess differences for each dependent variable, with playing time (starter vs non-starter players) used as a fixed factor, and athlete, week, and team asrandom factors. The results showed that total weekly TL(d = 1.23-2.04), weekly ML(d = 4.65-5.31), training monotony (d = 0.48-1.66) and training strain (d = 0.24-1.82) for RPEbreath, RPEleg and RPEcog were higher for starters in comparison with non-starters (p = 0.01). Coaches involved in elite female football should consider implementing differentials RPE monitoring strategiesto optimize the weekly load distribution for starters and non-starters and to introduce compensatory strategies to equalise players` total weekly load.